2005
DOI: 10.1007/s10654-004-6519-2
|View full text |Cite
|
Sign up to set email alerts
|

Has the prevalence of migraine and tension-type headache changed over a 12-year period? A Danish population survey

Abstract: The prevalence of tension-type headache but not of migraine increased. The increase in migraine and tension-type headache frequency suggests a higher individual and societal impact of primary headaches now, than 12 years ago.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

27
193
4
12

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 251 publications
(236 citation statements)
references
References 28 publications
(48 reference statements)
27
193
4
12
Order By: Relevance
“…A reduction in headache frequency led to the development of an episodic pattern from a chronic pattern of headaches. 36 The same findings were reported in another Danish study of 740 individuals with headache followed up for 2 years. 37 Similar data were also recorded in the USA.…”
Section: Discussionsupporting
confidence: 75%
“…A reduction in headache frequency led to the development of an episodic pattern from a chronic pattern of headaches. 36 The same findings were reported in another Danish study of 740 individuals with headache followed up for 2 years. 37 Similar data were also recorded in the USA.…”
Section: Discussionsupporting
confidence: 75%
“…We found, for example, that migraine was related to familial factors, anxiety, and stress reactivity, whereas TTH was associated with neck or back injury in early childhood [30]. Other studies have found that the prevalence of migraine is higher in women than men yet for tension-type headaches women are only slightly more affected than men [37,38]. The risk factors for TTH appear to be different from those for migraine.…”
Section: Headache Classificationmentioning
confidence: 48%
“…Hence the apparent lack of distinction between TTH and migraine in clinical settings may reflect referral bias [37]. Population-based evidence of significant differences in epidemiological characteristics suggests that migraine and tension-type headaches are distinct entities [36,38]. We found, for example, that migraine was related to familial factors, anxiety, and stress reactivity, whereas TTH was associated with neck or back injury in early childhood [30].…”
Section: Headache Classificationmentioning
confidence: 77%
“…It is estimated that 78% of the general population is affected by tension type headaches [48]. Majority have infrequent episodic TTH (once a month or less) with 24 to 37% experiencing headaches several days a month and 10% suffers once weekly.…”
Section: Acupuncture In Tension Type Headachesmentioning
confidence: 99%
“…Chronic TTH evolves from episodic headaches and is defined as occurring on more than 15 days a month for at least three months. Chronic TTH is rare and the lifetime prevalence is estimated to be 2-3% [48,49]. TTH are defined as recurrent headaches of mild to moderate intensity, usually bilateral and pain is often described as of pressing or tightening quality.…”
Section: Acupuncture In Tension Type Headachesmentioning
confidence: 99%